Beyond simple work in the field: the life story of a young man from Florestan Fernandes/Para além do simples trabalho no campo: a história de vida de um jovem assentado do Florestan Fernandes - Alexsandro do Nascimento Macedo; Edijan Santos Costa (Diversitas Journal, 2020)
This article brings the result of theoretical and methodological discussions, as well as field activities that were developed during the Special Topic in History Teaching course of the Professional Master's Course in History Teaching - PROFHISTÓRIA, from the Federal University of Sergipe - UFS, taught by professors Dr. Joaquim Tavares da Conceição and Dr. Paulo Heimar Souto. Using the oral history method, a sixteen-year-old man, resident of the Florestan Fernandes Settlement, located in the rural area of the municipality of Canindé de São Francisco / SE, was interviewed. The main objective is to understand, through the analysis of the testimony given by him, aspects of work, leisure and education that are part of the daily life of young people in the mentioned context. Based on the oral history method, it was possible to verify the peculiarities of forms of leisure, the concern that young people have with h the preservation of the Caatinga, as well as the forms of work practiced by the residents of the settlement.